Penerapan teknologi tepat guna untuk unit usaha pembuatan dodol nanas di Kota Dumai - Wetri Febrina; Azmi Azmi (Unri Conference Series: Community Engagement, 2019)
Pineapple is an agricultural product that is widely cultivated in Riau, including in Dumai. Most pineapples from Dumai was sold as fresh fruit consumed by the local citizen, because it’s demographically difficult to compete with pineapple production from Kampar which is closer to the provincial capital, Pekanbaru. The excess production at harvest results in some fruit not being sold and wasted. Likewise, fruit damage due to the wrong way in harvesting. This encourages people through farmer groups and community activity units to treat pineapple fruit into snacks such as pineapple dodol, pineapple chips, pineapple jam, and others. The problem lies in many workstations, long working time and simple equipment. As a result, the profits generated weren’t comparable to the resources deployed. The purpose of this activity was to assist the pineapple dodol’s maker by designing and making production aids such as pineapple peeler and dodol pineapple mixer. The method of this activity was counseling and training. The object/partner in this activity was UKM Kemuning which is located at Jl. Muslim No.1 Mundam, Kecamatan Medang Kampai, Dumai. The results obtained from this activity was an increase in the working time of making dodol from previously 3-4 days to just 1-2 days.